The gifts of the Jews : how a tribe of desert nomads changed the way everyone thinks and feels - Cahill, Thomas (Oxford, UK : Lion Hudson, 1998)
Taking us first to Sumer in the third millennium, Cahill explores a civilization in which life is seen - as it was in all ancient societies - as part of an endless cycle of birth and death: time perceived as a wheel, spinning ceaselessly, never altering its course - until the ancient Jews dramatically change that perception. When Abraham hears the Voice of God speaking the unexpected words "Go forth," the concept of an unknown future takes hold and Western civilization is born. From this insight the Jews evolve a new vision of men and women with unique destinies - a vision that thousands of years later will inspire the Declaration of Independence and our hopeful belief in progress and the sense that tomorrow can be better than today. Thomas Cahill narrates this momentous shift with compelling stories, insights, and humor, and draws us closer to such powerful biblical personalities as Abraham and Sarah, Moses and Miriam, David, Amos, Isaiah, Naomi, and Ruth.
Introduction: The Jews Are It -- I. The Temple in the Moonlight: The Primeval Religious Experience -- II. The Journey in the Dark: The Unaccountable Innovation -- III. Egypt: From Slavery to Freedom -- IV. Sinai: From Death to Life -- V. Canaan: From Tribe to Nation -- VI. Babylon: From Many to One -- VII. From Then Till Now: The Jews Are Still It -- The Books of the Hebrew Bible -- Index of Biblical Citations.
Includes indexes.
Keywords: Bible. -- history of biblical events; Judaism -- history -- to AD 70.; Jews -- history -- to AD 70.; Civialisation -- Jewish influences